Terminologi Pemuridan Dalam Injil Matius 28:19-20 - Arman Susilo; Nova Huwae (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2022)
The term disciple in Matthew 28:19 has a deep theological meaning. The term inspired the birth of the missionary work carried out by the church. As a result, the church continues to grow throughout the world. Uniquely, the command to make disciples is only recorded by the Gospel of Matthew, not recorded in the other two Synoptic Gospels. It is necessary to carry out an in-depth study of the concept of discipleship recorded by Matthew. In addition, there are some grammatical errors that Matthew uses, giving rise to a prejudice that the idea in Matthew 28:16-20 is invalid. Then, the long period of time between the events recorded and the year of writing is also a special problem in responding to the idea of ​​making disciples of nations. Allegedly, the author's motivation is the key in understanding the use of the term